Asia Pacific trade facilitation report 2019 bridging trade finance gaps through technology. - Kim, Kijin (Metro Manila, Philippines Asian Development Bank, 2019)
Trade facilitation initiatives can make an important contribution to economic growth and poverty reduction by lowering trade costs and increasing trade flows. This report reviews trade facilitation progress in the region, including recent trends in paperless trade and transit facilitation and the impact of trade facilitation initiatives on trade costs. It also features a special chapter on how trade finance gaps especially prevalent for small and medium sized enterprises can be bridged by technology, and the supporting policies and actions required to make this happen.
Keywords: Small business -- Asia -- Pacific Area; Service industries -- Asia; Electronic books